The Relationship between Working Memory and Confrontation Naming Following Traumatic Brain Injury - Ehsan Hemmati; Davood Sobhani-Rad; Sadegh Seifpanahi; Hamideh Ghaemi (Shiraz University of Medical Sciences, 2018)
Background: The prefrontal cortex is very susceptible to traumatic brain injury (TBI), upon which many cognitive and executive functions including planning, information processing, language, memory, attention, and perception will be impaired. Working memory (WM) is associated with high levels of cognitive processes such as language and naming process communication. In the present study, the correlation between WM and confrontation naming was investigated following TBI. Methods: The current research was a prescriptive-analytic cross-sectional study examining 20 TBI patients within the age range 18-45 years. The samples were selected from Iran, the city of Mashhad, between 2013 and 2016. The participants with a score 23 or higher in Mini-Mental State Examination (MMSE) were assessed through Persian naming test and sub-tests from the Wechsler Memory Scale. The collected data were analyzed by SPSS16 software. Results: There was a significant association between subtests of confrontation naming involving 'Correct answers without cue' and WM (P<0.05), 'Wrong answers' and WM (P<0.05), as well as 'Total correct answers' and WM (P<0.05). Conclusion: The present study indicated modest significant correlations between measures of confrontation naming and WM. These findings provide direction for future studies on the nature of naming deficits following brain injury.